Financial returns to household inventory management - Baker, Scott R.; Johnson, Stephanie; Kueng, Lorenz (Journal of Financial Economics, 2024)
Households tend to hold substantial amounts of non-financial assets in the form of consumer goods inventories that are unobserved by traditional measures of wealth, about $725 on average for products covered by our sample. Such holdings can eclipse total financial assets among households in the lowest income quintile. Households can obtain significant financial returns from strategically shopping and managing these inventories. In addition, they choose to maintain liquid savings—household working capital—not just for precautionary motives but also to support this inventory management. We demonstrate that households earn high marginal returns from investing in household working capital, well above 20% at low levels of inventory, though these marginal returns decline rapidly as inventory increases. Nevertheless, average returns from inventory management are high—about 50% for the typical household—and affect household portfolio returns substantially for all but the top income and asset quintiles. We provide evidence from scanner and survey data that supports this conclusion. For many households, working capital is therefore an important asset class that has been largely ignored by the household finance literature, and inventory management provides them with an alternative to investing in risky financial markets at low levels of liquid wealth.